Selected Abstracts of the 2nd Congress of joint European Neonatal Societies (jENS 2017); Venice (Italy); October 31-November 4, 2017; Session "Neurology and Follow-up" - Various Authors, — (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2017)
Selected Abstracts of the 2nd Congress of joint European Neonatal Societies (jENS 2017); Venice (Italy); October 31-November 4, 2017 58th ESPR Annual Meeting, 7th International Congress of UENPS, 3rd International Congress of EFCNI ORGANIZING INSTITUTIONS European Society for Paediatric Research (ESPR), European Society for Neonatology (ESN), Union of European Neonatal & Perinatal Societies (UENPS), European Foundation for the Care of Newborn Infants (EFCNI) ORGANIZING COMMITTEE Luc Zimmermann (President of ESPR), Morten Breindahl (President of ESN), Manuel Sánchez Luna (President of UENPS), Silke Mader (Chairwoman of the Executive Board and Co-Founder of EFCNI) SCIENTIFIC COMMITTEE Virgilio P. Carnielli (Congress President Chair), Pierre Gressens (Past Scientific President), Umberto Simeoni, Manon Benders, Neil Marlow, Ola D. Saugstad, Petra Hüppi, Agnes van den Hoogen Session "Neurology and Follow-up" ABS 1. PRETERM BIRTH AND THE TIMING OF PUBERTY • E. James, C. Wood, H. Nair, T. Williams ABS 2. NEONATAL PAIN, OPIOID AND ANAESTHETIC EXPOSURE; WHAT REMAINS IN THE HUMAN BRAIN AFTER THE WHEELS OF TIME? • G.E. van den Bosch, D. Tibboel, J.C. de Graaff, H. El Marroun, A. van der Lugt, T. White, M. van Dijk ABS 3. DEPRESSION DURING PREGNANCY AND DNA METHYLATION CHANGES IN CORD BLOOD • A.-C. Viuff, G. Sharp, D. Raj, K.J. Kyng, L.H. Pedersen, T.B. Henriksen, C.L. Relton ABS 4. PREVENTION OF CEREBRAL PALSY: FEASIBILITY OF UMBILICAL CORD BLOOD STEM CELLS AND UMBILICAL CORD MESENCHYMAL STROMAL CELLS • H. Shintaku, M. Nabetani, T. Hamazaki, S. Kusuda, M. Tamura, S. Watabe, M. Hayakawa, Y. Sato, M. Tsuji, A. Taguchi, H. Ichiba, O. Akira, R. Mori, A.Taki, T. Mukai, T. Nagamura-Inoue ABS 5. NO GENDER-RELATED DIFFERENCES IN FETAL CORPUS CALLOSUM THICKNESS: IN-UTERO MRI STUDY • R. Bercovitz, R. Achiron, C. Hoffmann, A. Achiron ABS 6. NEUROMOTOR PROFILE OF HIGH-RISK INFANTS AT TERM OR NEAR TERM • I. Ereno, W.Y. Teh ABS 7. THE PREDICTIVE VALUE OF SEVERE BRONCHOPULMONARY DYSPLASIA FOR NEUROLOGICAL IMPAIRMENT IN 2-YEARS-OLD VERY PRETERM INFANTS IS HIGHER WHEN DIAGNOSED AT 40 THAN AT 36 WEEKS’ POSTMENSTRUAL WEEKS • A.M. Malavolti, D. Bassler, R. Arlettaz-Mieth, G. Faldella, B. Latal, G. Natalucci ABS 8. PSYCHOSOCIAL OUTCOME OF INFANTS WITH CONGENITAL MALFORMATIONS AFTER POSTNATAL SURGICAL REPAIR • N. Doberschuetz, A. Allendorf, R. Dewitz, B. Wittekindt, U. Rolle, R. Schloesser ABS 9. THERAPEUTIC HYPOTHERMIA AND HEARING IMPAIRMENT: INCIDENCE AND ASSOCIATED FACTORS • M.P. Fitzgerald, G. Norman, C. Mc Garvey, A. Reynolds, M. King, B. Hayes ABS 10. PRETERM INFANTS 33-35 WEEKS’ GESTATION WITH SEVERE HYPOXIC-ISCHEMIC ENCEPHALOPATHY TREATED WITH HYPOTHERMIA DO NOT PRESENT MORE ORGAN DYSFUNCTION THAN TERM NEWBORNS • M. Alsina, A. Martin-Ancel, M. Leon, G. Arca, E. Perez, A. García-Alix ABS 11. IMPACT OF ENVIRONMENTAL FACTORS ON MOTOR AND COGNITIVE PERFORMANCE OF LATE PRETERM INFANTS • M.M. Santos, C. Corsi, A.C. Campos, N.A.C.F. Rocha ABS 12. THROMBOCYTOPENIA IS ASSOCIATED WITH SEVERE RETINOPATHY OF PREMATURITY CLINICALLY; IN MICE PLATELET TRANSFUSION SUPPRESSES RETINOPATHY • P. Lundgren, R. Liegl, S. Klevebro, G. Hellgren, C. Löfqvist, C. Mannheimer, Y. Sun, Z.-J. Liu, M.C. Sola-Visner, B. Hallberg, L.E.H. Smith, A. Hellström ABS 13. COGNITIVE AND BEHAVIORAL ASPECTS OF EXECUTIVE FUNCTIONING AT AGE 6.5 YEARS IN CHILDREN BORN EXTREMELY PRETERM: A SWEDISH NATIONAL PROSPECTIVE STUDY (EXPRESS) • A. Farooqi, F. Serenius, M. Adamsson, M. Hafström, U. Åden, K. Stjernqvist ABS 14. EARLY AMPLITUDE INTEGRATED ELECTROENCEPHALOGRAM AS A PREDICTOR OF BRAIN INJURY IN NEWBORNS WITH VERY LOW BIRTH WEIGHT: A COHORT STUDY • R.C. Silveira, L.V. Magalhaes, M.I. Winckler, J.A. Bragatti, R.S. Procianoy ABS 15. NEONATAL ADMISSIONS FOR HYPOXIC ISCHEMIC ENCEPHALOPATHY: WEEKEND AND OUT OF HOURS EFFECT • F. Ceroni, M. Parmar, S. Narayanan, N. Merchant ABS 16. WHICH PARTS OF GROWTH SHOULD BE MONITORED FOR NEURODEVELOPMENT OF PRETERM INFANTS • I.G. Song, H.R. Yoon, Y.M. Yoon, J.S. Shin, S.H. Shin, E.K. Kim, H.S. Kim ABS 17. TARGETED METHYLATION TESTING OF A 154 PATIENT’S COHORT WITH CLINICAL FEATURES OF IMPRINTING DISORDERS: EVIDENCE OF MULTILOCUS METHYLATION DEFECTS • A.Touati, S. Nouri, F. Chioukh, M. Haddaji Mastouri, N. Ben Salah, S. Trabelsi, S. Hammami, S. Mougou, M. Gribaa, N. Guedich, H. Seboui, A. Nouri, K. Monastiri, A. Saad, D. H’mida-Ben Brahim ABS 18. STEINERT MYOTONIC DYSTROPHY (DM1): WHAT ABOUT CARDIAC INVOLVEMENT? • H. Hadj Abdallah, Y. Halleb, N. Ben Salah, F.Z. Chioukh, K. Ben Ameur, F. Kallel, L. Ben Slamia, S. Hidar, M. Bellallah, S. Nouri, S. Ben Amor, A. Hsin, M. Grira, H. Ajmi, S. Zardi, S. Abroug, N. Mahdhaoui, H. Sboui, S. Ben Ammou, K. Mestiri, A. Saad, D. H’mida ABS 19. ATYPICAL BRAIN DEVELOPMENT ASSOCIATED WITH PRENATAL METHADONE EXPOSURE • V. Monnelly, D. Anblagan, A. Quigley, E. Cooper, H. Mactier, S. Semple, M. Bastin, J. Boardman ABS 20. CHARACTERISATION OF THE NEONATAL CORPUS CALLOSUM (CC) USING MAGNETIC RESONANCE IMAGING (MRI) AND CRANIAL ULTRASOUND (US) • M. Mills, V. Pelling, L. Harris, J. Smith, H. Rabe, R. Fernandez ABS 21. COGNITIVE TRAJECTORIES FROM INFANCY TO EARLY ADULTHOOD FOLLOWING BIRTH BEFORE 26 WEEKS OF GESTATION • L. Linsell, S. Johnson, D. Wolke, H. O’Reilly, J. Morris, J. Kurinczuk, N. Marlow ABS 22. INHIBITORY CONTROL AT 20 MONTHS PREDICTS VP/VLBW AND TERM ADULTS’ ATTENTION, IQ, AND WEALTH AT AGE 26 YEARS • J. Jaekel, N. Baumann, P. Bartmann, D. Wolke ABS 23. HEAD MIDLINE POSITION FOR THE PREVENTION OF GERMINAL MATRIX-INTRAVENTRICULAR HEMORRHAGE IN PRETERM INFANTS: A SYSTEMATIC REVIEW AND META-ANALYSIS • O. Romantsik, M.G. Calevo, M. Bruschettini ABS 24. MOTOR FUNCTION AT EARLY SCHOOL AGE IN EXTREMELY PRETERM BORN CHILDREN WITHOUT MAJOR IMPAIRMENTS IN RELATION TO PERINATAL FACTORS: NATIONAL POPULATION-BASED STUDY (EXPRESS) • J. Bolk, A. Farooqi, M. Hafström, U. Åden, F. Serenius ABS 25. COGNITIVE FUNCTIONING IN ADOLESCENTS BORN MODERATELY PRETERM AT 32-26 WEEKS’ GESTATION: A SWEDISH REGIONAL POPULATION BASED CASE CONTROL STUDY • M. Adamsson, B. Hägglöf, M. Bäckman, A. Farooqi ABS 26. EARLY RISK FACTORS FOR ADVERSE NEUROMOTOR DEVELOPMENT IN TERM INFANTS AFTER MODERATE HYPOXIC-ISCHAEMIC ENCEPHALOPATHY • A. Matic ABS 27. THERAPEUTIC HYPOTHERMIA IN BABIES WITH HYPOXIC-ISCHAEMIC ENCEPHALOPATHY: EVIDENCE AND CLINICAL PRACTICE • K. Ghazal, A. Panickar, S. Garg ABS 28. EFFECT OF DEHYDROEPIANDROSTERONE AND ITS SULFATE ESTER ON NEONATAL HYPOXIC-ISCHEMIC BRAIN INJURY – PRELIMINARY DATA • A. Posod, M. Lachinger, B. Vejnoska, E. Huber, M. Urbanek, U. Kiechl-Kohlendorfer, E. Griesmaier ABS 29. LONG-TERM EFFECTS OF NEONATAL COMPLICATIONS ON BRAIN GROWTH AT 10 YEARS OF AGE IN CHILDREN BORN EXTREMELY PRETERM • N. Padilla, C. Jimenez-Espinoza, H. Kvanta, U. Adén ABS 30. SECRETONEURIN SERUM CONCENTRATIONS CORRELATE WITH ABNORMAL NEURODEVELOPMENTAL OUTCOME AT THE AGE OF 24 MONTHS IN TERM NEONATES WITH ASPHYXIA • K. Wechselberger, A. Schmid, M. Höck, A. Posod, M. Urbanek, R. Fischer-Colbrie, V. Neubauer, U. Kiechl-Kohlendorfer, E. Griesmaier ABS 31. SCREENING C677T POLYMORPHISM IN METHYLENETETRAHYDROFOLATE REDUCTASE GENE IN TAIWAN POPULATION • C.Y. Chuang, C.C. Hung, Y.N. Su, P.N. Tsao ABS 32. GENETIC CONTRIBUTIONS TO THE DEVELOPMENT OF INTRAVENTRICULAR HEMORRHAGE IN PRETERM NEWBORNS • D. Szpecht, J. Gadzinowski, A. Seremak-Mrozikiewicz, G. Kurzawińska, K. Drews, M. Szymankiewicz ABS 33. MRI-DIAGNOSED WHITE MATTER LESIONS IN THE BRAIN OF VLBW BABIES: RISK FACTOR ANALYSIS • A. Parodi, S. Raffa, M. Malova, A. Sannia, M. Severino, G. Morana, D. Tortora, M.G. Calevo, A. Rossi, L.A. Ramenghi ABS 34. A NEW EVALUATION INDEX FOR LEFT-RIGHT UNEQUAL VENTRICULOMEGALY IN VERY LOW BIRTH WEIGHT INFANTS: ASSOCIATION WITH WALKING DISABILITIES AT 1.6 YEARS OF CORRECTED AGE • T. Ikuta, M. Mizobuchi, Y. Katayama, S. Yoshimoto, T. Ioroi, M. Yamane, T. Morisawa, A. Takatera, M. Ueda, A. Shibata, K. Maeyama, K. Fujioka, N. Nishimura, K. Iijima, I. Morioka ABS 35. EPIGENETIC DIFFERENCES IN CORD BLOOD OF NEWBORNS EXPOSED TO ANTIDEPRESSANT MEDICATION DURING PREGNANCY – A STUDY IN THE AARHUS BIRTH COHORT • A.-C. Viuff, G.C. Sharp, L.H. Pedersen, N.H. Staunstrup, K.J. Kyng, D. Rai, C.L. Relton, T.B. Henriksen ABS 36. AUTISM SPECTRUM DISORDER IN EX-PRETERMS IS PRECEDED BY ALTERED NEONATAL BRAIN VOLUMES IN MULTIMODAL ASSOCIATION AREAS AND ALTERED PATTERNS OF BRAIN ASYMMETRY • N. Padilla, E. Eklöf, G. Mårtensson, S. Bölte, H. Lagercrantz, U. Åden ABS 37. COGNITIVE OUTCOME IN ADULTS BORN WITH VERY LOW BIRTH WEIGHT OR SMALL FOR GESTATIONAL AGE • S. Weider, A.M.W. Lærum, K.A.I. Evensen, S. Lydersen, A.M. Brubakk, M.S. Indredavik ABS 38. PERFORMANCE OF THE GERMAN VERSION OF THE PARCA-R QUESTIONNAIRE AS A COGNITIVE SCREENING TOOL IN VERY PRETERM INFANTS AT 2 YEARS OF CORRECTED AGE • G. Natalucci, N. Bechtel, C. Borradori-Tolsa, M. Bickle-Graz, M. Adams, S. Grunt for the Swiss Neonatal Network & Follow-Up Group ABS 39. NEURODEVELOPMENT IN 7-YEAR OLD CHILDREN BORN WITH MARGINALLY LOW BIRTH WEIGHT • J. Starnberg, M. Norman, B. Westrup, M. Domellöf, S.K. Berglund ABS 40. EARLY NEONATAL EEG MARKERS FOR DYSLEXIA RISK: A PILOT STUDY • S. Martini, P. Cyr, L. Brightman, L. Amunts, G. Belteki, T. Austin, V. Leong ABS 41. MATERNAL SWIMMING DURING PREGNANCY PROTECTS THE NEONATAL RAT BRAIN FROM HYPOXIC-ISCHEMIC INJURY • E.F. Sanches, Y. van de Looij, A. Silva, J. Romero, S.V. Sizonenko ABS 42. PERSISTENT MATHEMATICS LEARNING DIFFICULTIES FROM CHILDHOOD TO ADOLESCENCE IN VERY PRETERM CHILDREN IN MAINSTREAM SCHOOL • S. Clayton, L. Cragg, C. Gilmore, N. Marlow, V. Simms, R. Spong, S. Johnson ABS 43. PRENATAL METHADONE EXPOSURE AND NEURODEVELOPMENTAL AND NEUROIMAGING OUTCOMES: A SYSTEMATIC REVIEW • V. Monnelly, R. Hamilton, F. Chappell, H. Mactier, J. Boardman ABS 44. NEURODEVELOPMENT FOLLOW-UP FOR HIGH-RISK BABIES IN LIVERPOOL: A QUALITATIVE STUDY. FOUNDATION STUDY “FOLLOW-UP FOR NEURODEVELOPMENTALLY AT RISK INFANTS OF NEONATAL CARE” • A. Komoriyama, F. Paize, C. Dewhurst, M. Gladstone ABS 45. COLD-INDUCIBLE RBM3 PROMOTES NEUROGENESIS AFTER BRAIN HYPOXIC-ISCHEMIA/REPERFUSION INJURY • X. Zhu, C. Brégère, J. Yan, U. Fisch, J. Kapfhammer, R. Guzman, S. Wellmann ABS 46. REACHING SKILLS OF INFANTS BORN VERY PRETERM PREDICT NEURODEVELOPMENT AT 3 YEARS • Y. Fredriksson Kaul, K. Rosander, H. Grönqvist, K. Strand Brodd, L. Hellström-Westas, C. von Hofsten ABS 47. RETINOPATHY OF PREMATURITY AND NEUROCOGNITIVE FUNCTION AT AGE 10 IN CHILDREN BORN EXTREMELY PRETERM • M. Holm, T.S. Morken, R.M. Joseph, M.E. Msall, T.M. O´Shea, K.C.K. Kuban, O. Dammann, E.N. Allred, A. Leviton ABS 48. UNDERSTANDING ADHD AND ASD IN VERY PRETERM CHILDREN FROM A SENSORY PROCESSING PERSPECTIVE: A CONTROLLED NEUROPSYCHOLOGICAL STUDY • T. Bröring, K. Oostrom, M. Königs, E. van Dijk-Lokkart, H. Lafeber, A. Brugman, J. Oosterlaan ABS 49. SOCIAL-EMOTIONAL DEVELOPMENT IN VERY PRETERM INFANTS DURING EARLY INFANCY • P.H. Gray, D.M. Edwards, M. Pritchard ABS 50. TOUCHSCREENS FOR COGNITIVE ASSESSMENT OF TODDLERS • D.M. Twomey, C. Wrigley, C. Ahearne, R. Murphy, M. de Haan, N. Marlow, D.M. Murray ABS 51. NEUROPROTECTIVE INTERVENTION AFTER HYPOXIA-ISCHEMIA MAY CHANGE INTRACEREBRAL METABOLIC MEASURES IN A NEWBORN PIGLET MODEL • T.C. Andelius, N. Bøgh, M.V. Pedersen, C. Omann, V.E. Hjortdal, M. Pedersen, T.B. Henriksen, K.J. Kyng ABS 52. TWO-YEAR OUTCOME OF EXTREMELY PRETERM INFANTS < 26 WEEKS OF GESTATION BORN IN SWITZERLAND: IS INTENSITY OF PERINATAL CARE ASSOCIATED WITH INCREASED NEURODEVELOPMENTAL IMPAIRMENT? • G. Natalucci, T.M. Berger, C. Borradori-Tolsa, M. Bickle-Graz, S. Grunt, R. Gerull, D. Bassler, M. Adams for the Swiss Neonatal Network & Follow-Up Group ABS 53. SELF-REPORTED WIDESPREAD PAIN IN ADULTS BORN EARLY AND LATE PRETERM • K.A.I. Evensen, M. Tikanmäki, K. Heinonen, H.-M. Matinolli, M. Sipola-Leppänen, A. Lano, D. Wolke, M. Vääräsmäki, J.G. Eriksson, S. Andersson, M.-R. Järvelin, P. Hovi, K. Räikkönen, E. Kajantie ABS 54. BRAIN VOLUMES BY CEREBRAL MRI AND CORRELATIONS WITH PSYCHIATRIC SYMPTOMS IN LOW BIRTHWEIGHT ADULTS • A.M.W. Lærum, L.M. Rimol, S.K. Reitan, A. Brubakk, K.A.I. Evensen, K.J. Bjuland, S. Lydersen, J. Skranes, M.S. Indredavik ABS 55. POSTURE AND MOBILITY INFLUENCE ON ATTENTION ABILITIES IN HEALTHY 7 YEARS OLD CHILDREN • H. Ceyte, J. Rosenbaum, S. Caudron, J.-M. Hascoet ABS 56. SURGICAL DECISION MANAGEMENT IN CHIARI TYPE 2 MALFORMATION: A SINGLE CENTER EXPERIENCE • S.A. Ozdemir, N. Ozdemir, A. Karadag, E.A. Ozer ABS 57. EFFECTS OF NEURAL STEM CELL MEDIA ON HYPOXIC INJURY IN RAT HIPPOCAMPAL SLICE CULTURES • N.M. Lee, S.A. Chae, H.J. Lee ABS 58. A NOVEL CEREBRAL ULTRASOUND SCORING SYSTEM IS ASSOCIATED WITH NEUROLOGICAL OUTCOME IN NEONATES WITH HYPOXIC-ISCHEMIC ENCEPHALOPATHY • K. Annink, F. Groenendaal, M. Lequin, D. Vijlbrief, L. de Vries, M. Benders, J. Dudink ABS 59. MONITORING THE ENERGY METABOLISM IN PLASMA FROM NEWBORNS WITH HYPOXIC-ISCHEMIC ENCEPHALOPATHY (HIE) DURING THERAPEUTIC HYPOTHERMIA • Á. Sánchez-Illana, A. Núñez-Ramiro, M. Cernada, A. Parra, E. Valverde, D. Blanco, M.T. Moral-Pumarega, F. Cabañas, H. Boix, A. Pavon, M. Chaffanel, I. Benavente-Fernández, I. Tofe, B. Loureiro, J.R. Fernández-Lorenzo, B. Fernández-Colomer, J. Kuligowski, M. Vento; the HYPOTOP Study Group ABS 60. PHOSPHOLIPID SYNTHESIS RELATED BIOMARKERS IN PLASMA FROM NEWBORNS WITH HYPOXIC-ISCHEMIC ENCEPHALOPATHY • J. Kuligowski, Á. Sánchez-Illana, J.D. Piñeiro-Ramos, A. Núñez-Ramiro, M. Cernada, A. Parra, E. Valverde, D. Blanco, M.T. Moral-Pumarega, F. Cabañas, H. Boix, A. Pavon, M. Chaffanel, I. Benavente-Fernández, I. Tofe, B. Loureiro, J.R. Fernández-Lorenzo, B. Fernández-Colomer, M. Vento; the HYPOTOP Study Group ABS 61. CEREBROSPINAL FLUID LACTATE IN NEWBORN AND PRETERM INFANTS. PILOT DATA • G. Uclés, D. Arjona, R. Borrego, R. Díaz, M.D. Sánchez-Redondo, A. Escobar ABS 62. DIFFERENCES BETWEEN INTRAUTERINE AND EXTRAUTERINE GROWTH OF THE CEREBELLUM • A.I. Toma, I. Cuzino, A. Cozinov, R.G. Olteanu ABS 63. CAN DIFFERENCES IN EARLY FUNCTIONAL CONNECTIVITY IN HEALTHY NEWBORNS EXPOSED TO OLFACTORY STIMULATION HELP US UNDERSTAND CRYING BEHAVIOUR AT 6 WEEKS OF LIFE? • L. Freitas, A. Adam-Darque, F. Grouiller, J. Sauser, F. Lazeyras, P. Pollien, C.L. Garcia-Rodenas, G. Bergonzelli Degonda, D. Van De Ville, P. Hüppi, R. Ha-Vinh Leuchter ABS 64. LESS INVASIVE SURFACTANT ADMINISTRATION (LISA) NOT ONLY IMPROVES MORTALITY AND MORBIDITY BUT ALSO NEURODEVELOPMENTAL OUTCOME OF PRETERM INFANTS • K. Klebermass-Schrehof, A. Grill, M. Hayde, N. Haiden, A. Flunt, R. Fuiko, S. Brandstetter, A. Berger ABS 65. REDUCED PREVALENCE OF SEVERE INTRAVENTRICULAR HEMORRHAGE IN VERY PRETERM INFANTS DELIVERED AFTER MATERNAL PREECLAMPSIA • E. Morsing, K. Maršál, D. Ley ABS 66. COGNITIVE STABILITY IN CHILDREN WITH CONGENITAL HEART DISEASE • N. Naef, C. Schaefer, V. Rousson, R. Liamlahi, S. Polentarutti, I. Beck, V. Bernet, H. Dave, W. Knirsch, B. Latal ABS 67. PERIPHERAL T CELL DEPLETION BY FINGOLIMOD IS ASSOCIATED WITH EXACERBATED HYPOXIC-ISCHEMIC BRAIN INJURY IN NEONATAL MICE • I. Bendix, M. Crasmöller, C. Köster, M. Serdar, U. Felderhoff-Müser, J. Herz ABS 68. DIFFERENTIATING THE PRETERM PHENOTYPE: DISTINCT PROFILES OF DEVELOPMENT AFTER LATE AND MODERATELY PRETERM BIRTH • S. Johnson, G. Waheed, B.N. Manktelow, D. Field, N. Marlow, E.S. Draper, E.M. Boyle ABS 69. NEONATAL NEUROIMAGING IN SYMPTOMATIC CONGENITAL CMV (cCMV) AND ITS CORRELATION WITH OUTCOME: EMPHASIS ON WHITE MATTER DISEASE • A. Alarcon, A. Garcia-Alix, M. Martinez-Biarge, I. van Straaten, F. Cabañas, J. Quero, L. de Vries ABS 70. INTRANASALLY APPLIED MESENCHYMAL STEM CELLS MIGRATE TO INJURED BRAIN REGIONS OF NEWBORN NON-HUMAN PRIMATES • N. Wagenaar, F. van Bel, M. Benders, C. Blanco, D. McCurmin, S. Mustafa, F. Groenendaal, L. de Vries, C. Heijnen, C. Nijboer ABS 71. EARLY CRANIAL ULTRASOUND AND MRI AT TERM IN VERY PRETERM INFANTS: DIAGNOSIS OF BRAIN INJURY VERSUS NEURODEVELOPMENTAL OUTCOME AT 12 AND 24 MONTHS CORRECTED GESTATIONAL AGE • K. Chatzidimitriou, A. Chebsey, D. Odd, M. El Brookle, M. Likeman, A. Heep ABS 72. CRANIAL ULTRASOUND AT DAY 7 AND CLINICAL MRI AT TERM IN VERY PRETERM INFANTS BORN AT LESS THAN 28 WEEKS: VENTRICULOMEGALY IS RELATED TO SUBTLE BRAIN PATHOLOGY AND UNFAVORABLE DEVELOPMENTAL OUTCOME AT 24 MONTH • K. Chatzidimitriou, A. Chebsey, D. Odd, M. El Brookle, M. Likeman, A. Heep ABS 73. AUTOPHAGY INHIBITION PROTECTS IN A PRETERM RAT MODEL OF EXCITOTOXIC BRAIN INJURY • C. Descloux, V. Ginet, J. Puyal, A.C. Truttmann ABS 74. VALIDITY OF THE KOREAN DEVELOPMENTAL SCREENING TEST FOR VERY LOW BIRTH WEIGHT INFANTS • C.Y. Kim, J.H. Hwang, E. Jung, B.S. Lee, K.S. Kim, A.R. Kim ABS 75. INTERACTION BETWEEN ACUTE THERAPEUTIC HYPOTHERMIA AND A DELAYED MESENCHYMAL STEM CELL THERAPY IN NEONATAL HYPOXIA-ISCHEMIA • J. Herz, C. Köster, B.S. Reinboth, M. Dzietko, I. Bendix, U. Felderhoff-Müser ABS 76. IMPACT OF NEONATAL WHITE MATTER INJURY AND BRAIN VOLUMES TO SCHOOL-AGE NEURODEVELOPMENT IN CHILDREN WITH CONGENITAL HEART DISEASE • N.H.P. Claessens, S.O. Algra, T.L. Ouwehand, N.J.G. Jansen, P. Moeskops, I. Išgum, R. Schappin, I.C. van Haastert, M.J.C. Eijsermans, F. Groenendaal, L.S. de Vries, M.J.N.L. Benders ABS 77. ASYNCHRONY AND SPECTRAL EEG COHERENCE IN TERM NEONATES WITH INTRAUTERINE GROW RESTRICTION • B. Reyes Millán, J.R. Castro Conde, C. González Campo, I. Quintero Fuentes, N.L. González González, D. González Barrios ABS 78. MUSIC EFFECTS IN PRETERM INFANTS’ BRAIN: A STRUCTURAL NEUROIMAGING INVESTIGATION • J. Almeida, N. Kunz, L. Lordier, A. Darque, F. Lazeyras, P. Hüppi ABS 79. CONGENITAL HEART DEFECTS AND ACADEMIC PERFORMANCE IN A NATIONWIDE COHORT OF 458,318 DANISH CHILDREN • N.B. Matthiesen, S.H. Larsen, T.B. Henriksen, C.C. Bach, J.R. Ostergaard, V. Hjortdal ABS 80. PROGNOSTIC VALUE OF EARLY CONVENTIONAL PROTON MAGNETIC RESONANCE SPECTROSCOPY IN COOLED ASPHYXIATED NEWBORNS • H. Barta, A. Jermendy, M. Kolossvary, L.R. Kozak, A. Lakatos, U. Meder, G. Rudas, M. Szabo ABS 81. CYTOKINES TRAJECTORIES IN NEWBORNS WITH HYPOXIC-ISCHEMIC ENCEPHALOPATHY: THE ROLE OF HYPOTHERMIA • S. Perrone, S. Cornacchione, M.D. Weiss, R. Candace, M. Longini, F. Proietti, M. Calderisi, G. Buonocore ABS 82. COLD-INDUCIBLE RBM3 AUGMENTS IGF2 EXPRESSION IN NEURAL STEM CELLS BY INTERACTING WITH IMP2 IN AN RNA-DEPENDENT MANNER • J. Yan, X. Zhu, A. Zelmer, J. Kapfhammer, S. Wellmann ABS 83. EARLY POSTOPERATIVE AMPLITUDE-INTEGRATED ELECTROENCEPHALOGRAPHY: BIOMARKER OF NEW BRAIN INJURY IN NEONATES WITH CONGENITAL HEART DISEASE • N.H.P. Claessens, L. Noorlag, L. Weeke, M. Toet, J.M.P.J. Breur, M.J.N.L. Benders, F. Groenendaal, N.J.G. Jansen, L.S. de Vries ABS 84. STABILITY OF AUTISM DIAGNOSIS IN CHILDREN BORN VERY-PRETERM FROM AGE 2 TO 4 YEARS • M. Pritchard, H. Haydon, T. de Dassel, E. Beller, F. Bogossian, L. Johnston, J. Paynter, S. Russo, J.G. Scott ABS 85. ASSOCIATION BETWEEN TRANSIENT NEONATAL HYPOGLYCEMIA AND ADVERSE NEUROLOGICAL DEVELOPMENT AT 2-6 YEARS OF AGE • R. Wickström, B. Skiöld, G. Petersson, O. Stephansson, M. Altman ABS 86. PERINATAL ASSOCIATIONS WITH BRAIN GROWTH EVALUATED BY SEQUENTIAL CRANIAL ULTRASONOGRAPHY IN VERY PRETERM INFANTS • R. Cuzzilla, A.J. Spittle, K.J. Lee, S. Rogerson, F.M. Cowan, L.W. Doyle, J.L.Y. Cheong ABS 87. NEUROFILAMENT SERUM LEVELS AS BIOMARKER OF NEURONAL INJURY IN VERY PRETERM BORN INFANTS • A. Depoorter, C. Barro, R. Neumann, J. Kuhle, S. Wellmann ABS 88. PREDICTING THE DEVELOPMENT OF CEREBRAL PALSY: A COMPARISON BETWEEN DTI-MRI AND EARLY HAND ASSESSMENT IN INFANTS WITH UNILATERAL PERINATAL BRAIN INJURY • B. van Gasselt, N. Wagenaar, C. Verhage, M. Benders, F. Groenendaal, L. de Vries, N. van der Aa ABS 89. MICRORNA PANEL VALIDATION IN HYPOXIC ISCHEMIC ENCEPHALOPATHY • M.P. O’Sullivan, A.M. Looney, G. Moloney, B. Hallberg, G. Clarke, G.B. Boylan, D.M. Murray ABS 90. OUTBORN PRETERM INFANTS WITH POST-HAEMORRHAGIC VENTRICULAR DILATATION: ARE THEY TRANSFERRED TOO LATE? • A. Parodi, M. Malova, A. Sannia, A. Cama, M. Ravegnani, C. Bellini, L.A. Ramenghi ABS 91. CEACAM1 EXPRESSION IN THE CEREBELLUM • S. Prager, B.B. Singer, I. Bendix, J. Herz, U. Felderhoff-Müser ABS 92. LONG-TERM NEURODEVELOPMENTAL OUTCOMES AMONG YOUNG ADULTS BORN PRETERM • M. Tei, S. Negro, M.C. Muraca, M.G. Gatti, D. Urilli, G. Buonocore, S. Perrone ABS 93. LOW-GRADE IVH AND LOW-GRADE CBH: WHICH INFLUENCE ON GRIFFITHS SCORE AT 2 YEARS OF AGE? • A. Parodi, M. Malova, S. Uccella, L. Boeri, E. De Grandis, A. Sannia, M. Severino, G. Morana, D. Tortora, A. Rossi, E. Veneselli, L.A. Ramenghi ABS 94. GENETIC CAUSES IN NEWBORNS WITH EPILEPTIC ENCEPHALOPATHIES • A. Soltirovska Salamo, D. Paro-Panjan ABS 95. OUTCOME AT FIVE YEARS OLD IN A SWISS NATIONAL COHORT OF VERY PRETERM INFANTS BORN IN 2006 • M.P. Pittet, M. Adams, M. Bickle-Graz, S. Grunt, I. Mürner-Lavanchy, R.E. Pfister, G. Natalucci, C. Borradori Tolsa ABS 96. PLACENTAL HISTOLOGY FINDINGS AS POSSIBLE RISK FACTORS FOR MRI-DETECTED BRAIN LESIONS IN VLBW INFANTS • A. Parodi, M. Re, D. Brignole, M.P. Brisigotti, M.G. Calevo, M. Malova, A. Sannia, M. Severino, G. Morana, D. Tortora, A. Rossi, E. Fulcheri, L.A. Ramenghi ABS 97. SYSTEMIC INFLAMMASOME ACTIVATION IN NEONATAL ENCEPHALOPATHY • M. O’Dea, L. Kelly, J.J. O’Leary, E.J. Molloy ABS 98. LONGITUDINAL STUDY OF BRAIN TISSUE VOLUMES IN PRETERM INFANTS AND THEIR RELATION WITH NEONATAL RISK FACTORS AND NEURODEVELOPMENTAL OUTCOME • L. Gui, F. Lazeyras, P.S. Hüppi, C. Borradori ABS 99. DELINEATING THE BEHAVIOURAL PHENOTYPE AMONG CHILDREN BORN EXTREMELY PRETERM • J. Trickett, D. Wolke, C. Hollis, N. Marlow, S. Johnson ABS 100. NANOMOLECULAR SIGNALLING IN THE DEVELOPING BRAIN: CHARACTERISTICS OF EXOSOMES IN THE CEREBROSPINAL FLUID OF PRETERM INFANTS • R. Spaull, B. McPherson, A. Clayton, J. Uney, O. Cordero-Llana, A. Heep ABS 101. BEDSIDE MONITORING OF CEREBRAL METABOLISM IN NEONATES AT RISK FOR HYPOXIC-ISCHEMIC ENCEPHALOPATHY • M. El-Dib, S.J. Blackwell, F. Yi, R. Vyas, C.G. Ha, B. Walsh, T.E. Inder, P.E. Grant, S.L. Ferradal ABS 102. POSTNATAL MR-IMAGING AND ADC MEASURES IN CONGENTIAL CYTOMEGALOVIRUS INFECTION PROVIDE AN ADDED DIAGNOSTIC VALUE ON CEREBRAL ULTRASOUND IN CHARACTERIZING WHITE MATTER DISEASE • C. Martins, J. Schneider, M. Bickle Graz, M. Kobas, S. Asner, A.C. Truttmann ABS 103. COMPARISON OF 1-DIMENSIONAL AND 2-DIMENSIONAL SONOGRAPHIC (US) AND MRI MEASUREMENTS OF THE CEREBELLUM IN TERM NEWBORNS • B. Reulecke, R. Fernandez, M. Mills, V. Pelling, H. Rabe, L. Harris ABS 104. MILD HYPOXIC ISCHAEMIC ENCEPHALOPATHY AND LONG TERM NEURODEVELOPMENTAL OUTCOME-A SYSTEMATIC REVIEW • J. Conway, B.H. Walsh, M. Dozier, G.B. Boylan, D.M. Murray ABS 105. NEURODEVELOPMENTAL AND SENSORY OUTCOME AT TWO YEARS IN VLBW BABIES: CORRELATIONS WITH BRAIN LESIONS DETECTED AT TERM MRI • M. Malova, L. Ceschi, C. Traggiai, S. Uccella, A. Parodi, A. Sannia, L. Boeri, E. De Grandis, M. Severino, G. Morana, D. Tortora, M.G. Calevo, A. Rossi, E. Veneselli, C. Bellini, L.A. Ramenghi ABS 106. PREVALENCE OF AUTISM IN EXTREME PRETERM CHILDREN BORN IN STOCKHOLM 2004-2007 • E. Eklof, A. Hedfors Moretti, H. Lagercrantz, S. Bolte, U. Aden ABS 107. CEREBRAL AUTOREGULATION IN ASPHYXIATED NEONATES TREATED WITH HYPOTHERMIA • A. Hendriksen, L. Dix, W. Baerts, F. van Bel, F. Groenendaal, P. Lemmers ABS 108. HYPERECHOGENICITY OF THE LENTICULOSTRIATE ARTERIES: INCIDENCE AND CLINICAL IMPACT IN A TERTIARY NICU • P. Triantafyllidou, M. Papadopoulou, S. Gantseva-Patsoura, F. Kokkori, E. Varxalama, M. Theodoraki, A. Gounaris ABS 109. A MIXED LIPID EMULSION – RICH IN DOCOSAHEXAENOIC ACID (DHA) – AND ITS EFFECT ON BRAIN MATURATION IN EXTREMELY LOW BIRTH WEIGHT INFANTS • C. Binder, A. Repa, V. Giordano, M. Thanhaeuser, A. Kreissl, N. Haiden, A. Berger, N. Longford, K. Klebermass-Schrehof ABS 110. IMPACT OF PARTURITION ON MATERNAL NEURONAL INTEGRITY • K.S. Evers, S. Fouzas, C. Barro, J. Kuhle, U. Fisch, O. Lapaire, S. Wellmann ABS 111. THE EFFECT OF MORPHINE ON EARLY BRAIN ACTIVITY IN EXTREMELY PRETERM INFANTS: AN OBSERVATIONAL MULTICENTER STUDY • M.L. Tataranno, L.S. de Vries, L. Hellström-Westas, O. Dammann, M. Toet, F. Groenendaal, N.H.P. Claessens, V. Fellman, K. Sävman, M.J.N.L. Benders ABS 112. PERSISTENT MONOCYTE AND NEUTROPHIL ACTIVATION IN SCHOOL AGE CHILDREN POST NEONATAL ENCEPHALOPATHY • Z. Zareen, V. Mc Eneaney, N.A. Taher, L. Kelly, D. Sweetman, D. Doherty, E. Molloy ABS 113. BLOOD BASED PROTEINS THAT DIFFERENTIATE INFLAMMATION-SENSITIZED HYPOXIA VERSUS HYPOXIA ALONE WITHIN THE 6 H THERAPEUTIC WINDOW IN A PIGLET MODEL • I. Lingam, A. Avdic-Belltheus, K. Martinello, C. Meehan, S. Ragab, I. Tachtsidis, C. Tann, M. Hristova, B. Fleiss, T. Wolfs, B. Kramer, N. Klein, H. Hagberg, P. Gressens, N.J. Robertson ABS 114. BLOOD PLASMA PROFILE OF TEMPORAL MICRORNA EXPRESSION OF INFLAMMATION IN LIPOPOLYSACCHARIDE SENSITISED PORCINE MODEL OF HYPOXIC ISCHAEMIC ENCEPHALOPATHY • A. Avdic-Belltheus, I. Lingam, C. Meehan, K. Martinello, S. Ragab, I. Tachtsidis, C. Tann, M. Hristova, B. Fleiss, T. Wolfs, B. Kramer, N. Klein, H. Hagberg, P. Gressens, N.J. Robertson ABS 115. ARE THE 2 YEAR GRIFFITHS SCORES OF BABIES WITH CEREBELLAR HAEMORRHAGE (CBH) AND INTRAVENTRICULAR HAEMORRHAGE (IVH) SIGNIFICANTLY DIFFERENT COMPARED TO THOSE OF BABIES SUFFERING FROM ISOLATED IVH? • S. Uccella, A. Parodi, M. Malova, L. Boeri, E. De Grandis, C. Traggiai, A. Sannia, M. Severino, G. Morana, D. Tortora, A. Rossi, E. Veneselli, L.A. Ramenghi ABS 116. INCIDENCE AND CHARACTERISTICS OF INFANTS WITH RETINOPATHY OF PREMATURITY IN CROATIA • M. Vucinovic, L.J. Znaor, A. Vucinovic ABS 117. SYSTEMIC ALTERATIONS IN HYPOXIA-INDUCIBLE FACTOR 1α EXPRESSION AND THE NLRP3 INFLAMMASOME IN POST NEONATAL ENCEPHALOPATHY IN SCHOOL AGE CHILDREN AND RESPONSE TO MELATONIN IN VITRO • L. Russo, V. Mc Eneaney, Z. Zareen, L.A. Kelly, E.J. Molloy ABS 118. BRAIN GROWTH AND RELATIONSHIPS WITH ILLNESSES AND NEURODEVELOPMENT OUTCOME • R. D’Ascenzo, B. Pieroni, A. Pianesi, A. Peretti, L. Regnicolo, G. Polonara, M.J. Benders, V.P. Carnielli